Investigation of the proteins associated with epithelial-mesenchymal transition in skin tumors (Annals of Medical Research, 2021)
Aim: While epithelial-mesenchymal transition (EMT) is associated with the complex morphogenetic events during embryogenesis, EMT has also been shown to play an important role in the progression of epithelial cancers. There have been few studies examining ZEB1 and SMAD protein expressions in skin tumor tissues in the literature, and there are no studies evaluating GIT1 protein expression.Materials and Methods: Thirty-seven pieces of squamous cell carcinoma(SCC), 34 pieces of basal cell carcinoma(BCC), 11 pieces of actinic keratosis(AK), 9 pieces of in situ SCC(SCCIS) and 7 pieces of normal skin tissue were included in this study.Results: A statistically significant difference was found between the SMAD1, AREB6 and GIT1 H-scores values of the individuals in the five groups. The levels of SMAD1, AREB6 and GIT1 were higher in SCC than in the control group. In binary comparisons, the SMAD1 H-score values of BCC, SCCIS groups were statistically significantly higher than normal skin. GIT1 H-score values of SCC and BCC groups were significantly higher than normal skin.Conclusion: In skin tumors, EMT is an ever-active mechanism. It is thought that this mechanism is highly controlled in SCC, a more aggressive type of cancer, than in BCC. These results suggest that the investigation of genes related to SMAD1, AREB6 and GIT1 may be useful for research into new molecular targets for the treatment and prevention of metastasis in nonmelanotic skin tumors.